Stimulation of non-transferrin iron uptake by iron deprivation in K562 cells - Kovar, Jan; Neubauerova, Jitka; Cimburova, Marketa; Truksa, Jaroslav; Balusikova, Kamila; Horak, Jiri (Blood cells, molecules & diseases, 2006)
We tested the effect of iron deprivation on the uptake of iron from ferric citrate by human erythroleukemia K562 cells. The iron uptake after 24-h preincubation in defined iron-free medium was approximately 2-3x higher than after the preincubation in control transferrin-containing medium. The preincubation of K562 cells in iron-free medium together with the inhibitor of protein synthesis cycloheximide completely abrogated the stimulation of the iron uptake. The preincubation in iron-free medium resulted in a slight decrease (20%) of DMT1 mRNA level. The level of Dcytb, ferroportin and hephaestin mRNA did not exert any significant change. We also did not find any significant effect on the protein level of DMT1, Dcytb, ferroportin and hephaestin. We conclude that iron deprivation stimulates the uptake of non-transferrin iron in K562 cells and that this stimulation depends on protein synthesis. It seems that the expression of an unknown or seemingly unrelated protein(s) is involved.
Keywords: železo; časové faktory; transferin; nádorové buňky kultivované; vztahy mezi strukturou a aktivitou; K562 Cells; proteiny regulující obsah železa; Time Factors; Cycloheximide; buňky K562; Tumor Cells, Cultured; Transferrin; cykloheximid; lidé; Iron-Regulatory Proteins; Iron; Humans; Structure-Activity Relationship